The Influence of Brand Image and Brand Awareness on Brand Loyalty in Packaged Drinking Water Ades in Surabaya City - Marsetio Paramandhana Putra; Sugeng Purwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study aims to understand the influence of brand image and brand awareness on the brand loyalty of Ades bottled drinking water in Surabaya. The method employed is a quantitative study with a sample of 100 individuals using purposive sampling technique. Data were collected through questionnaires distributed to residents of Surabaya. The variables used include brand image (X1) and brand awareness (X2) as independent variables, and brand loyalty (Y) as the dependent variable. Data analysis using the Partial Least Squares (PLS) method indicates that the better the brand image and brand awareness, the higher the brand loyalty of Ades bottled drinking water in Surabaya.